A multilevel moderated mediation model of developmental human resource management practices in the hotel industry - Usman, Muhammad; Karatepe, Osman M.; Akhtar, Muhammad Waheed (Elsevier Sci Ltd, 2026)
Using social information processing theory, our paper develops and tests a multilevel moderated mediation model that investigates the interrelationships of developmental human resource management (DHRM), affective organizational commitment (AOC), loyal boosterism, proactive customer service performance (PCSP), and leader conscientiousness. Data came from hotel frontlines employees (FLEs) and their supervisors in Morocco. The results from structural equation modeling suggest that all hypotheses were corroborated. As hypothesized, DHRM practices fostered FLEs' loyal boosterism and PCSP. As expected, AOC partly mediated the impacts of DHRM practices on loyal boosterism and PCSP. Consonant with the study hypotheses, leader conscientiousness strengthened the positive influences of DHRM practices on AOC, while it moderated the effects of DHRM practices on loyalt boosterism and PSCP via AOC. These results ensure significant insights for boosting DHRM practices and their outcomes to reach customer satisfaction and retention. These results also ensure significant implications for theory and offer future research directions.
Keywords: Affective organizational commitment; Developmental human resource management; practices; Leader conscientiousness; Loyal boosterism; Multilevel analysis; Proactive customer service performance; Social information processing theory